Assessment of tomato potato psyllid Bactericera cockerelli (Hemiptera: Triozidae) food plant range by comparing feeding behaviour to survival of early life stages. Issue 2 (28th November 2017) - Sandanayaka, Manoharie; Connolly, Patrick G; Withers, Toni M
Abstract: The tomato potato psyllid (TPP, Bactericera cockerelli ) is an important vector of Candidatus Liberibacter solanacearum. TPP is a phloem sap feeder, with an extensive host plant range. Measuring host plant feeding via electrical penetration graph (EPG) is a potentially less time‐consuming method compared with traditional ways of assessing the host range of sap‐feeding insects through feeding bioassays. Feeding behaviour of Candidatus Liberibacter solanacearum‐positive adult TPP was measured using EPG technique on seven plant species: capsicum, eggplant, Cape gooseberry, poroporo, black nightshade (all Solanaceae), kumara (Convolvulaceae) and coprosma (Rubiaceae). Coprosma was used as a plant species of unknown host status. EPG data were analysed for three recording durations (5, 10 and 15 h). Data recorded for 10 h provided the most accurate prediction of subsequent feeding behaviour, allowing discrimination between host plants which could support feeding by TPP and non‐host plants that could not. EPG feeding behaviour was then contrasted with the survival of early life stages of TPP on four of the seven plant species under a choice situation on whole plants. The one discrepancy between the two methods for separating host from non‐host plants was with Cape gooseberry. EPG suggested that Cape gooseberry was as acceptable for feeding by TPP as capsicum, but whole‐plant assays showed survival of early nymph stages on Cape gooseberry was poor. EPG has merit as a tool for rapid assessment of plants at risk of feeding damage from a phloem sap feeder. However, a degree of experience is required to operate this technology successfully and to interpret the output data. The wire attachment on the insects may have a negative influence on initial plant contact. Therefore, a long recording time around 10 h may be required to offset this limitation.